The Relationship between Early Pregnancy and Postpartum Anxiety: A Systematic Review - Mumtazah, Nabilah Zhafirah Al; Husen, Shifa Nabila; Fitriana, Farida (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2024)
Background: Anxiety in pregnancy has many adverse effects, both on maternal mental health and birth outcomes, as well as being a risk factor for maternal depression. The period of pregnancy and childbirth is said to be a period of life that has the potential for pregnant women to experience stress. Early pregnancy occurs in young women aged <20 years. This study aims to analyze and examine the relationship between early pregnancy and postpartum anxiety using a systematic review method. Method: This research is a systematic review with PICO including: (1) Population: pregnant women; (2) Intervention: Early pregnancy; (3) Normal age pregnancy; (4) Postpartum blues. The databases used are Google Scholar, PubMed, and GARUDA. Inclusion criteria include full text in Indonesian and English with research subjects being pregnant women with anxiety. The exclusion criteria in this study were articles published under the last five years. Results: A total of 9 articles stated that there was a relationship between early pregnancy and postpartum anxiety. The average level of anxiety during pregnancy is quite high, and approaches a severe anxiety score. Anxiety levels decreased immediately after delivery, but there was no further decrease until the late postpartum period.